Ramón González Peą : (a) el hombre / Víctor Salazar ; prólogo de Belarmino Tomás ; epílogo de Ramón Lamoneda - Tomás Alvarez, Belarmino (1887-1950) Lamoneda, Ramón; Salazar, Víctor
Precede al título: El presidiario número 317